29.9k views
1 vote
Find the derivative of the cube
root of x using first principle.


1 Answer

4 votes

We have to compute the limit


\displaystyle \lim_(h\to 0) \frac{\sqrt[3]{x+h}-\sqrt[3]{x}}{h}

We want to use the cube difference formula:


a^3-b^3 = (a - b)(a^2 + ab + b^2)

So, we can multiply both numerator and denominator as follows


\frac{\sqrt[3]{x+h}-\sqrt[3]{x}}{h} = \frac{\left(\sqrt[3]{x+h}-\sqrt[3]{x}\right)\left(\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}\right)}{h\left(\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}\right)}

The numerator is now the difference of cubes, so we have


\frac{x+h-x}{h\left(\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}\right)} = \frac{h}{h\left(\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}\right)} = \frac{1}{\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}}

As h approaches zero, we have


\displaystyle \lim_(h\to 0)\frac{1}{\sqrt[3]{(x+h)^2}+\sqrt[3]{x(x+h)}+\sqrt[3]{x^2}} = \frac{1}{\sqrt[3]{(x+0)^2}+\sqrt[3]{x(x+0)}+\sqrt[3]{x^2}} = (1)/(3√(x^2))

User Jered
by
6.1k points